Analysis of forest management plans for environmental sustainability - Díaz-Mariño, Juan Pablo; Hernández-García, Diego (Revista de Ciencias Agrícolas, 2026)
Today, environmental care, conservation, and improvement are three key factors in humankind’s survival, including sustainable forest management as a crucial tool for maintaining environmental balance in terms of biodiversity, climate, and human well-being. This study was conducted aiming to explore the theoretical and methodological frameworks of forest harvesting, natural resource management plans, and environmental improvement plans across different regions worldwide. The PRISMA methodology was used, which allowed for the analysis of relevant information from various recognized scientific databases. Understanding and evaluating the effectiveness of forest harvesting and environmental improvement plans is essential, particularly for promoting forest sustainability and environmental conservation. The variables focused on different geographical contexts: Europe, Asia, Africa, North and Central America, South America, Colombia, and the department of Santander. The studies analyzed identified research processes focused on environmental improvement and conservation as the main trend. These processes reflect a growing concern and commitment among organizations, governments, environmental leaders, and the general community, who seek to work on the conservation of forest resources and their benefits for ecosystems and people’s communities. In addition, there is a strengthening of environmental awareness and an increasing focus on progress related to sustainable development indicators.